Proses Pembelajaran Menulis Esai Argumentatif Menggunakan Model Problem Based Learning dan Model VIII Problem Based Learning pada Siswa Kelas XI SMA Nurul Iman NW Tammimi Lombok Tengah - Maknunah, Baiq Roviatun; Adawiyah, Rabiyatul; Setiyadi, DB Putut; Hersulastuti, Hersulastuti; Haryono, Purwo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the effectiveness of the Problem Based Learning (PBL) model in learning to write argumentative essays. This study employs a quantitative approach with a one group pre-test post-test design. The subjects of the research are all students of class XI at SMA Nurul Iman NW Tammimi Lombok Tengah, totaling 20 people. Data collection techniques include tests, observations, and documentation. The statistical test used to test the hypothesis is the t-test. The analysis results show that the t-count value (3.257) is greater than the t-table value (1.729), which means there is a significant difference between the results of the pre-test and post-test. Thus, the alternative hypothesis (Ha) is accepted, namely that there is a significant influence of the PBL model on students' argumentative essay writing skills. In conclusion, (1) the PBL model is effective for teaching argumentative essay writing, and (2) this model is more capable of improving student learning outcomes compared to conventional methods.